2006
DOI: 10.1007/s11094-006-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of nitrogen-containing derivatives of methyl dehydroabietate

Abstract: The biological activity of a series of new amino derivatives of dehydroabietic acid has been studied. 12-N,N-Diethylaminoacetyl-8,11,13-abietatrien-18-oate hydrochloride produces a calming effect, shows pronounced anxiolytic activity, and exhibits antipyretic action comparable with that of the reference drug (analgin).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Up to date, RA-derived compounds with different pharmacological effects—anti-inflammatory [77], antimicrobial [12,78], fungicidal [12,22,23,79], anxiolytic [80], antiviral [23], antitumor [23,43,81], and anti-angiogenic [82]—have been described. In addition, RA derivatives can be used as intermediates in the synthesis of bioactive compounds [13,83] and pharmaceuticals [84,85].…”
Section: Biotransformation Of Ras To Bioactive Compoundsmentioning
confidence: 99%
“…Up to date, RA-derived compounds with different pharmacological effects—anti-inflammatory [77], antimicrobial [12,78], fungicidal [12,22,23,79], anxiolytic [80], antiviral [23], antitumor [23,43,81], and anti-angiogenic [82]—have been described. In addition, RA derivatives can be used as intermediates in the synthesis of bioactive compounds [13,83] and pharmaceuticals [84,85].…”
Section: Biotransformation Of Ras To Bioactive Compoundsmentioning
confidence: 99%
“…Despite the numerous biological activities that have been reported for DAA (Kang et al, 2009;Ohwada et al, 2003;Savluchinske-Feio et al, 2007;Tagat et al, 1994;Takahashi et al, 2011;Tanaka et al, 2008;Tolmacheva et al, 2006;Wada et al, 1985), the anti-aging effect of DAA has surprisingly not been studied. We used the Caenorhabditis elegans (C. elegans) wild-type N2 strain as a model organism of aging, to observe the lifespan extension effects of DAA.…”
Section: Daa Extends the Lifespan Of Wild-type C Elegans N2mentioning
confidence: 99%
“…DAA improves diabetes and hyperlipidemia in obese diabetic mice (Kang et al, 2009), activates peroxisome proliferatoractivated receptor-γ (PPAR-γ) and stimulates insulin-dependent glucose uptake into 3T3-L1 adipocytes (Takahashi et al, 2011). DAA has also shown antiulcer, antimicrobial, anxiolytic, antiviral, and antitumor activities (Savluchinske-Feio et al, 2007;Tagat et al, 1994;Tanaka et al, 2008;Tolmacheva et al, 2006;Wada et al, 1985). Recent studies have confirmed that DAA is a chemical modulator that opens large-conductance calcium-activated BK channels (Ohwada et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DHA is a naturally occurring tricyclic diterpenic resin acid, which can easily be obtained from Pinus rosin or commercial disproportionated rosin [ 6 ]. Recently, DHA and its derivatives were claimed to possess a wide range of biological and pharmacological activities, such as antiprotozoal [ 7 ], antiulcer [ 8 ], anti-inflammatory [ 9 ], immunomodulatory, antiviral [ 10 ], antimicrobial [ 11 , 12 ], antifungal [ 13 ], anxiolytic [ 14 ], anti-aging [ 15 ], gastroprotective [ 16 ], and BK channel-opening [ 17 ] activities. In addition, in recent years a number of DHA derivatives have been reported to have anticancer activity in many human cancer cells such as cervical carcinoma cells, hepatocarcinoma cells, lung cancer cells, prostate cancer cells, ovarian cancer cells, and breast cancer cells [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%